Carbonation of Ammonium Diuranate Filtrate to Enhance Uranium Rejection by Nanofiltration - Runci Wang; Zhongwei Yuan; Xiang Meng; Taihong Yan; Weifang Zheng (Membranes)
A commercial polymeric nanofiltration membrane (NF270, DuPont) was employed for uranium removal from ammonium diuranate filtrate (ADUF). Carbonate supplementation through ammonium carbonate addition enhanced uranium rejection via formation of uranyl–carbonate coordination complexes. Systematic speciation analysis of uranium species in ADUF was conducted, coupled with calculation of the concentration polarization modulus to optimize ammonium carbonate dosage. The experimental results demonstrated that with 680 mg/L ammonium carbonate addition, the permeate uranium concentration decreased from 1.2 mg/L to 0.64 mg/L. This study confirms the technical feasibility of ADUF carbonation pretreatment for improving uranium retention efficiency in nanofiltration processes, achieving 46.7% reduction in uranium permeation flux.